Valorization of Camellia oleifera through integrated lignin extraction and tunable nanoparticle synthesis - Yougen Wu; Chengyun Deng; Xiaolu Zhao; Zhiping Wu; Zhenyan Ma; Hui Wang; Lishu Shao; Lin Zhang (AIP Advances)
The high-value utilization of Camellia oleifera, a major agroforestry waste, is critical for sustainable biomass management. This study presents a green integrated process for efficient lignin extraction and controllable nanoparticle synthesis via acidic solvent extraction and solvent-exchange nanotechnology. Two solvent systems were systematically optimized: HCl/1,4-dioxane achieved higher lignin purity (71.53%–73.52%) under optimal conditions (110 °C, 75 min, 90% solvent ratio), whereas p-TsOH/ethylene glycol low eutectic solvent (70 °C, 75 min, 65% ratio) yielded superior extraction efficiency (27.38%–28.74%). Subsequent solvent exchange enabled precise regulation of lignin nanoparticle morphology and size. Solvent polarity governed structural outcomes, with acetone producing elongated porous particles (153 ± 1 nm, PDI = 0.322) and tetrahydrofuran (THF) generating uniform spheres (140 ± 1 nm, PDI = 0.109). FTIR and zeta potential analyses revealed that tetrahydrofuran’s hydrophobic effects enhanced surface electronegativity (−37.5 mV), conferring exceptional colloidal stability (<1% size increase over 30 days). Synergistic optimization of THF/water ratio (50%) and lignin concentration (0.7 mg/ml) produced ultrasmall nanoparticles (80 nm, PDI = 0.082). This work elucidates the multiscale mechanism of solvent polarity in lignin extraction-nanostructuring and establishes a low-carbon pathway for agroforestry waste valorization. The methodology demonstrates significant potential for advancing green material synthesis and nanotechnology applications through biomass-derived functional nanomaterials.